WLS distribution system state estimator based on voltages or branch-currents: Accuracy and performance comparison - Pau, M.; Pegoraro, P. A.; Sulis, S. (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
This paper presents a comparison between the two main classes of Weighted Least Squares (WLS) state estimators used in distribution systems: state estimators based on node voltage state variables and estimators based on a state expressed in terms of branch-currents. In particular, the actual accuracy achieved for the estimated quantities by these estimators and their modified versions is analysed in details along with their performance, considering different types of real-time measurements (traditional or phasorial), different configurations of the measurement system and the impact of the network parameters uncertainty. Results obtained on two distribution networks with different scale, 18-bus and 95-bus, are presented and discussed.